Adrenomedullin 2 increases cardiac sympathetic nerve activity in parallel to heart rate in normal conscious sheep. Issue 10 (23rd May 2019) - Charles, Christopher J.; Jardine, David L.; Rademaker, Miriam T.; Mark Richards, A.
Abstract: Both adrenomedullin 2 (AM2) and sympathetic nerve activity (SNA) have been shown to be involved in regulating cardiovascular activity, but whether any interaction between these two systems exists remains to be determined. In this study, we examine the effects of intravenous AM2 infusions on SNA directed toward the heart (cardiac SNA (CSNA)) in healthy sheep studied in the conscious state. In response to AM2, arterial pressure was reduced ( P  = 0.005) with both heart rate ( P  < 0.001) and cardiac output ( P  < 0.001) increased compared with vehicle control response. CSNA burst frequency (bursts/min) and burst area/min both increased during infusion of AM2 (both P  < 0.001). However, correcting CSNA indices for concurrent heart rate changes resulted in CSNA burst incidence (bursts/100 beats) and burst area incidence (area/100 beats) being not significantly different between AM2 and control treatments. There were no significant differences demonstrated in plasma epinephrine or norepinephrine levels between the two study days. In conclusion, AM2 administered systemically to normal conscious sheep increases both CSNA and heart rate. However, correction for heart rate responses abrogates the rise in CSNA. It remains unclear whether AM2's primary effect is to act via the central nervous system to directly stimulate CSNA with resultant increase in heart rate, or to induce a rise in heart rate by other mechanisms. Abstract : We examined the effects of AM2 on cardiac sympathetic nerve activity (CSNA) and hemodynamics in normal conscious sheep. CSNA burst frequency (bursts/min) and burst area/min were increased in response to AM2 (both P  < 0.001). However, as correction for heart rate responses abrogates the rise in CSNA it remains unclear whether AM2's primary effect is to directly stimulate CSNA (via a central nervous system mechanism) resulting in increased heart rate, or to increase heart rate resulting in an increase in CSNA burst frequency.